2020
DOI: 10.1002/mp.14077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CT number calibration audit phantom in photon radiation therapy: A pilot study

Abstract: number. We established stoichiometric CT number calibration using only two materials because the accuracy of the process was determined not by the number of used materials but by the number of elements contained. The stoichiometric CT number calibration was comparable to the tissue-substitute calibration, with a dose difference less than 1%. An outline of the CT number calibration audit was demonstrated through a multi-institutional study. Conclusions: We established a new stoichiometric CT number calibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In Bibb et al (2011) up to 128 HU difference (average 28 HU) is reported for the same sample scanned either on the head phantom, or in the foam block. This difference, again, emphasizes the importance of well-defined scanning conditions, as is best demonstrated by CT quality control or electron density calibration phantoms used in radiotherapy planning ( Constantinou et al, 1992 ; Nakao et al, 2020 ), where the calibration cylinders are embedded into a water equivalent material in a cylindrical phantom of appropriate diameter.…”
Section: Discussionmentioning
confidence: 99%
“…In Bibb et al (2011) up to 128 HU difference (average 28 HU) is reported for the same sample scanned either on the head phantom, or in the foam block. This difference, again, emphasizes the importance of well-defined scanning conditions, as is best demonstrated by CT quality control or electron density calibration phantoms used in radiotherapy planning ( Constantinou et al, 1992 ; Nakao et al, 2020 ), where the calibration cylinders are embedded into a water equivalent material in a cylindrical phantom of appropriate diameter.…”
Section: Discussionmentioning
confidence: 99%
“…phantoms. The theoretical CT numbers using the stoichiometric CT number calibration method with three free parameters 25,28 were found to be more consistent with the measured CT numbers than conventional methods. 17,18 The standard tissue model 29…”
Section: Discussionmentioning
confidence: 63%
“…[21][22][23][24] A CT number calibration audit using a stoichiometric method was established for photon therapy, and a pilot study was conducted in five radiotherapy institutes. 25 In this study, the number of participating institutes, CT scanners, scan conditions, and TPSs were increased, and the interinstitute variations in the CT-ρ and CT-ρ e calibration curves were evaluated for each phantom vendor and TPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT number linearity test is carried out by graphing the mean CT number against the density of each phantom material [14,15]. A higher material density value should have a higher CT number, and vice versa [16][17][18].…”
Section: Introductionmentioning
confidence: 99%